Extraction techniques, structural features, and functional properties of collagenous derivatives from unconventional animal sources: a review - Indriani, Sylvia; Petcharat, Tanyamon; Andriani, Cynthia; Benjakul, Soottawat; Nalinanon, Sitthipong; Karnjanapratum, Supatra; Srisakultiew, Nattanan; Pongsetkul, Jaksuma (My University, 2026)
Collagenous derivatives (collagen, gelatin, and collagenous hydrolysate (CH)) are extensively used across the food, biomedical, and pharmaceutical industries. Traditionally, these have been sourced from porcine, bovine, and fish due to their ready availability and biocompatibility. However, conventional collagenous derivatives face ongoing challenges regarding sustainability, resource intensity, and socio-cultural perceptions. This has led to the exploration of alternative collagenous derivatives from unconventional sources, with a primary focus on evaluating their potential for yields, extractability, and functional properties, all of which are fundamental for future scale-up and alternative applications. This review summarizes alternative collagenous derivatives from unconventional animals, including amphibians, mollusks, echinoderms, insects, unconventional fish and byproducts, and reptiles. Their structures, extraction techniques, functional properties, and potential applications are comprehensively summarized, showcasing their ability to complement or even surpass conventional sources in specific uses. Additionally, the challenges and prospects for industrial application, emphasizing the sustainability of meeting growing collagen demand and encouraging further research into these promising alternative sources, were discussed. Unconventional collagenous derivatives demonstrate excellent and unique characteristics as alternatives to conventional ones. Type I collagen from amphibians, reptiles, and mollusks had superior thermal stability. Unconventional gelatin and CH also possess various bio-functionalities that can enhance their potential applications. The relatively low extraction yield could be addressed by increasing the concentration of chemicals or extraction time and incorporating green technology without causing an adverse impact on the quality. These findings indicate the potential applications of unconventional collagenous derivatives as food ingredients and supplements.
Keywords: Byproduct utilization; Collagen; Functional ingredients; Gelatin; Hydrolysates